FOOD AND FEEDING HABITS OF POLYNEMUS HEPTADACTYLUS CUV. AND VAL. - Kagwade, P V (Indian Journal of Fisheries, 2011)
The food and feeding habits of Polynemus heptadftctylus obtained from Bombay during the period 1956-58 were studied. Empty stomachs appeared in very high percentages in both the juveniles and adults all through the year. No period of active feeding at any time of the year was indicated either by the juveniles or adults. P. heptadactylus is carnivorous and its food composition varied widely, crustaceans ranking first, followed by fishes, polychaetes, molluscs and echinoderms. The planktonic forms, dominated by copepods, were observed in the food of juveniles alone. Crabs, molluscs and echinoderms were absent in the food of juveniles but present in that of adults. Amongst the crustaceans, Acetes indicus and Squilla spp. dominated in juveniles and penaeid and carid prawns followed by Squilla spp. in adults. Amongst the fish food B. macdeltandi ranked high in both the juveniles and adults. The differences in the food composition of juveniles and adults indicate their habitat preference.